Biological Pretreatment of Oil Palm Frond Fiber Using White-Rot Fungi for Enzymatic Saccharification - Hermiati, Euis; Anita, Sita Heris; Risanto, Lucky; Styarini, Dyah; Sudiyani, Yanni; Hanafi, Achmad; Abimanyu, Haznan (UI Scholars Hub, 2013)
Oil palm frond is one type of lignocellulosic biomass abundantly and daily available in Indonesia. It contains cellulose which can be converted to glucose, and further processed to produce different kinds of value –added products. The aim of this research is to study the effects of biological pretreatment of oil palm frond (OPF) fiber using Phanerochaete chrysosporium and Trametes versicolor on the enzymatic saccharification of the biomass. The OPF fiber (40-60 mesh sizes) was inoculated with cultures of the two fungi and incubated at 27 °C for 4 weeks. The samples were taken after 1, 2, 3, and 4 weeks of incubation. Chemical components of the biomass after pretreatment were analyzed. The saccharification of the pretreated samples using cellulase and β-glucosidase was performed in a water bath shaker at 50 °C for 48 hours. The concentration of reducing sugar increased with increasing of incubation time, either in those pretreated with culture of P. chrysosporium or with T. versicolor. Pretreatment of OPF fiber using single culture of T. versicolor for 4 weeks gave the highest reducing sugar yield (12.61% of dry biomass).